The Role Of Recuperation Functions In The Early Stages Of The Mine Planning Of An Iron Orebody - Fernando Humberto Muge (Society for Mining, Metallurgy & Exploration, 1982)
One of the problems that arises in the early stages of the mine planning before the determination of the mining exploitation method is to predict what will be the recoverable ore reserves in tonnage, grade and metal quantity, if the select ion is based upon block grades. The estimation of these recuperation or recoverable functions can act as an important planning tool in what concerns the appraisal of the consequences of ore-waste discrimination of individual blocks in a selective mining operation. Estimation methods of all these functions are discussed together with cross validation tests using the available information concerning a preliminary drilling campaign accomplished during the exploration stage of an iron orebody located in the North of Portugal (Moncorvo Orebody).